IgE actions on CD4+ T cells, mast cells, and macrophages participate in the pathogenesis of experimental abdominal aortic aneurysms. Issue 7 (24th June 2014) - Wang, Jing; Lindholt, Jes S; Sukhova, Galina K; Shi, Michael A; Xia, Mingcan; Chen, Han; Xiang, Meixiang; He, Aina; Wang, Yi; Xiong, Na; Libby, Peter; Wang, Jian‐An; et al.
<x xml:space="preserve">Abstract</x> This study demonstrates the pathologic role of IgE and its high affinity receptor FcεR1 in AAAs by activating MCs, macrophages but also CD4 and CD8 T cells and suggests anti‐IgE antibodies as future putative therapeutics for treatment. <boxed-text content-type="graphic" id="emmm201303811-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>